The specific grain-boundary electrical resistivity of Ni. Issue 9 (3rd May 2019) - Bakonyi, I.; Isnaini, V.A.; Kolonits, T.; Czigány, Zs.; Gubicza, J.; Varga, L.K.; Tóth-Kádár, E.; Pogány, L.; Péter, L.; Ebert, H.
ABSTRACT: The purpose of the present study was to provide a reliable value for the specific grain-boundary resistivity ρ SGBR of Ni metal. New results are presented on the room-temperature electrical resistivity of nanocrystalline (nc) Ni metal samples produced by electrodeposition with various grain sizes. These resistivity data were compared with previous reports on nc-Ni and all results were analysed according to the procedure of Andrews [ Phys. Lett. 19, 558 (1965)] who found that the resistivity increment due to grain boundaries is proportional to the grain-boundary surface area per unit volume which is, on the other hand, inversely proportional to the grain size. It is pointed out that the grain size directly accessible by transmission electron microscopy imaging is the relevant parameter for the evaluation of ρ SGBR whereas the crystallite size deduced from X-ray diffraction line broadening leads to an underestimation of ρ SGBR because coherency-breaking intragrain defects not contributing significantly to the resistivity also cause a line broadening. From the evaluation of the nc-Ni resistivity data at room temperature, we find that 4.45·10 −16 Ω·m 2 < ρ SGBR (Ni) < 6.2·10 −16 Ω·m 2 and our upper bound agrees exactly with the most recent calculated value in the literature.